Speech Processing in Modern Communication Challenges and Perspectives - Cohen, Israel; Benesty, Jacob; Gannot, Sharon; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
More and more devices for human-to-human and human-to-machine communications require some sophisticated algorithms. This is due to the fact that the acoustic environment in which we live in and communicate is extremely challenging. More than ever, the fundamental problems of acoustic echo cancellation, interference and noise suppression, and dereverberation need to be tackled rigorously. Researchers from diverse fields of speech processing contributed chapters addressing their specific topic of study, where research is very active. The topics include: speech enhancement in transient-noise and reverberant environments, single-channel blind source separation of speech and music signals, acoustic echo cancellation in double-talk scenarios, linear and nonlinear system identification in the short-time Fourier transform domain for acoustic echo cancellation, identification of the relative transfer function between sensors for beamforming in reverberant environments, microphone arrays in noisy reverberant environments, beamforming methods for spherical microphone arrays, and broadband source localization. This book has been edited for engineers, researchers, and graduate students who work on speech processing for communication applications. We hope that the readers will find many new and interesting concepts that are presented in this text useful and inspiring.
Linear System Identification in the Short-Time Fourier Transform Domain -- Identification of the Relative Transfer Function between Sensors in the Short-Time Fourier Transform Domain -- Representation and Identification of Nonlinear Systems in the Short-Time Fourier Transform Domain -- Variable Step-Size Adaptive Filters for Echo Cancellation -- Simultaneous Detection and Estimation Approach for Speech Enhancement and Interference Suppression -- Speech Dereverberation and Denoising Based on Time Varying Speech Model and Autoregressive Reverberation Model -- Codebook Approaches for Single Sensor Speech/Music Separation -- Microphone Arrays: Fundamental Concepts -- The MVDR Beamformer for Speech Enhancement -- Extraction of Desired Speech Signals in Multiple-Speaker Reverberant Noisy Environments -- Spherical Microphone Array Beamforming -- Steered Beamforming Approaches for Acoustic Source Localization.
Keywords: Engineering; Computer science; Acoustics; Telecommunication; Engineering; Signal, Image and Speech Processing; User Interfaces and Human Computer Interaction; Acoustics; Communications Engineering, Networks